Psychosocial factors at work and depression in three countries of Central and Eastern Europe - Pikhart, Hynek; Bobak, Martin; Pajak, Andrzej; Malyutina, Sofia; Kubinova, Ruzena; Topor, Roman; Sebakova, Helena; Nikitin, Yuri; Marmot, Michael (Social science & medicine (1982), 2004)
Psychosocial factors at work have been found to predict a range of health outcomes but their effect on mental health outcomes has not been extensively studied. This paper explores the relationship between psychosocial factors at work and depression in three countries of Central and Eastern Europe. The data come from a cross-sectional study of working men (n = 645) and women (n = 523) aged 45-64 years, randomly selected from population registers in Novosibirsk (Russia), Krakow (Poland) and Karvina-Havirov (Czech Republic). The questionnaire included questions on the effort and reward at work, job control, the full CES-D scale of depression, and a range of other characteristics. Linear regression was used to estimate the association between depression score and work characteristics: the logarithm of the effort-reward ratio, and continuous job control score. The means of the depression score were 10.5 for men and 14.2 for women. After controlling for age, sex and country, effort-reward ratio (logarithmically transformed) was strongly related to depression score; a 1 SD increase in the log transformed effort-reward ratio was associated with an increase in the depression of 2.0 points (95% CI 1.5; 2.4), and further adjustment did not materially change the effect. Job control was inversely associated with depression score in Poland and the Czech Republic (not in Russia) but the association was largely eliminated by controlling for socioeconomic characteristics. This study suggests that the effort-reward imbalance at work is related to prevalence of depression in these central and eastern European populations.
Keywords: Socioeconomic Factors; Russia; Cross-Sectional Studies; Workplace; Male; Personnel Delegation; Poland; Česká republika; psychický stres; Reward; socioekonomické faktory; Aged; Motivation; mužské pohlaví; senioři; deprese; Employment; průzkumy a dotazníky; Czech Republic; delegování pravomocí; hygiena práce; lidé; motivace; ženské pohlaví; odměna; Humans; Stress, Psychological; Occupational Health; průřezové studie; Rusko; zaměstnanost; Female; Surveys and Questionnaires; Polsko; Depression; lidé středního věku; pracoviště; Middle Aged